Contribution to the knowledge on the distribution of recent free-living freshwater ostracods (Podocopida, Ostracoda, Crustacea) in Slovenia - Nataša Mori; Claude Meisch (Natura Sloveniae)
An updated checklist of Recent free-living freshwater ostracods (Podocopida, Ostracoda, Crustacea) from Slovenia together with new records is presented. The new checklist is based on both the records extracted from the literature and the sampling in the field carried out during the last decade. The present checklist comprises 61 species. However, the eastern part of Slovenia and the surface waters are underrepresented. It is expected that the number of species will increase in the future.